(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Logic for gene expression analysis in a flurry. We developed a new method for analyzing gene expression data. To convert expression values into Quality descriptors, this method uses a fluid logic that can be evaluated using heuristic rules. We developed a model for identifying three different activators, repressors, and objectives in a data set for yeast gene expression in our experiments. The test predictions generated by an algorithm match the experimental data in the literature very well. Algorithms can identify a much larger number of transcription factors that could be identified at random in defining the function of unspecified proteins. Using only expression data in the form of clustering, this method allows the user to construct a linked network of genes. The interpretation of gene expression categorization models is typically difficult, however, it is an essential component of the analysis procedure. In five databases ranging in size, experimental origin, and physiological field, we investigate the effectiveness of micro rules fuzzy systems. The classifiers resulted in regulations that are simple to understand for biomedical researchers. The classifiers resulted in regulations that are simple to understand for biomedical researchers.